2018
DOI: 10.21608/mnj.2018.150616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Buerger Allen Exercise on Lower Limb Perfusion Among Patients With Type 2 Diabetes Mellitus

Abstract: Diabetes related lower extremity complication increase the risk for amputation which include peripheral neuropathy, peripheral vascular disease, and infection. Peripheral arterial disease is estimated to be 2 to 4 times more common in persons with diabetes than in others. Buerger Allen exercise intended to improve feet, legs circulation and relieve the symptoms in patients with lower limbs arterial insufficiency. Therefore, the aim of the study, evaluate the effect of Burger Allen exercise on lower limb perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This can be explained as a higher ABI value implies normal tissue perfusion; tissue and wound bed perfusion adequacy has been identified to be the most critical indicator of wound healing following foot and ankle surgeries by means of it increasing nutrients supply to tissues and cellular oxygenation which plays a fundamental role in the expansion of new capillaries, synthesis of collagen, and infection prevention and control thereby boosting wound regeneration leading to lower total wound score. This finding was in accordance with Zahran (2018) (15) who reported that, there was a significant negative correlation between patient's ABI and ulcer surface area before and after performing Buerger Allen exercises where p values were found to be (p= 0.027) in Pre-test and (p =0.035) in immediate posttest.…”
Section: Tablesupporting
confidence: 91%
See 1 more Smart Citation
“…This can be explained as a higher ABI value implies normal tissue perfusion; tissue and wound bed perfusion adequacy has been identified to be the most critical indicator of wound healing following foot and ankle surgeries by means of it increasing nutrients supply to tissues and cellular oxygenation which plays a fundamental role in the expansion of new capillaries, synthesis of collagen, and infection prevention and control thereby boosting wound regeneration leading to lower total wound score. This finding was in accordance with Zahran (2018) (15) who reported that, there was a significant negative correlation between patient's ABI and ulcer surface area before and after performing Buerger Allen exercises where p values were found to be (p= 0.027) in Pre-test and (p =0.035) in immediate posttest.…”
Section: Tablesupporting
confidence: 91%
“…They were alienated into two equivalent groups; 30 children for each group as following: It was established by the researcher after appraising the pertinent literature in order to assemble socio-demographic as well as clinical data of children. (15,16) (17,18) : was developed by the researcher after reviewing the pertinent literature; including data such as: -Capillary refill time (CRT): A CRT of 1 to 2 seconds is considered normal, while CRT of longer than 2 seconds indicates poor perfusion. -Local skin temperature: cold skin temperature is a characteristic indicator of peripheral vasoconstriction.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity is a significant risk factor for both type 1 and type 2 diabetes, exacerbating insulin resistance and contributing to earlier onset and increased severity of the disease. The prevalence of overweight and obesity among individuals with type 1 diabetes ranges from 25% to 80%, further complicating disease management (33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%